Dynamic and coordinated epigenetic regulation of developmental transitions in the cardiac lineage - Wamstad, Joseph A; Alexander, Jeffrey M; Truty, Rebecca M; Shrikumar, Avanti; Li, Fugen; Eilertson, Kirsten E; Ding, Huiming; Wylie, John N; Pico, Alexander R; Capra, John A; Erwin, Genevieve; Kattman, Steven J; et al. (Cell, 2012)
Heart development is exquisitely sensitive to the precise temporal regulation of thousands of genes that govern developmental decisions during differentiation. However, we currently lack a detailed understanding of how chromatin and gene expression patterns are coordinated during developmental transitions in the cardiac lineage. Here, we interrogated the transcriptome and several histone modifications across the genome during defined stages of cardiac differentiation. We find distinct chromatin patterns that are coordinated with stage-specific expression of functionally related genes, including many human disease-associated genes. Moreover, we discover a novel preactivation chromatin pattern at the promoters of genes associated with heart development and cardiac function. We further identify stage-specific distal enhancer elements and find enriched DNA binding motifs within these regions that predict sets of transcription factors that orchestrate cardiac differentiation. Together, these findings form a basis for understanding developmentally regulated chromatin transitions during lineage commitment and the molecular etiology of congenital heart disease.